Mind and hand : the birth of MIT - Stratton, Julius Adams, 1901-1994 (MIT Press, 2005)
The intellectual heritage of MIT: an account of "the flow of ideas" about science and education that shaped the Institute as it emerged and that inspires it today. The motto on the seal of the Massachusetts Institute of Technology, "Mens et Manus"--"mind and hand"--signals the Institute's dedication to what MIT founder William Barton Rogers called "the most earnest cooperation of intelligent culture with industrial pursuits." Mind and Hand traces the ideas about science and education that have shaped MIT and defined its mission--from the new science of the Enlightenment era and the ideals of representative democracy spurred by the Industrial Revolution to new theories on the nature and role of higher education in nineteenth-century America. MIT emerged in mid-century as an experiment in scientific and technical education, with its origins in the tension between these old and new ideas. Mind and Hand was undertaken by Julius Stratton after his retirement from the presidency of MIT and continued by Loretta Mannix after his death; Philip N. Alexander, of the MIT Program in Writing and Humanistic Studies, stepped in to complete the project. The combined efforts of these three authors have given us what Julius Stratton envisioned--"a coherent account of the flow of ideas" from which MIT emerged